Weak if any effect of estrogen on spatial memory in rats - Varga, Hedvig (Acta Biologica Szegediensis, 2002)
In a number of species, males appear to have spatial abilities that are superior to those of females. The favored explanation for this cognitive difference is hormonal: higher testosterone levels in males than in females. An alternative explanation focuses on the role of varying levels of estrogens in females during the estrus cycle; females perform as well as males on days of low estrogen, but more poorly on days of high estrogen. Other investigators have reported that estrogens improve both types of memory processes, which depend on the striatal (nonspatial navigation) and hippocampal (spatial) memory systems. Additionally, estrogens have been found to protect the working memory. These contradictory results initiated the present study, in which ovariectomized female rats were trained to escape in a Morris water maze. The daily trials were preceded by estradiol application in low doses (Experiment I) or in higher doses (Experiment II). In Experiment I, no differences at all were found between the latencies of the treated and control groups to reach a submerged platform in a Morris water maze. In Experiment II, however, the animals treated with the higher dose of estradiol showed a small deficit in the acquisition of the Morris water maze task. This study indicates that estradiol at around the physiological level has no effect on spatial learning and memory functions.